Transcutaneous Electrical Acupoint Stimulation for the Prevention of Postoperative Cognitive Dysfunction: A Systematic Review and Meta-Analysis - Zhang, Tiantian; Ou, Liang; Chen, Zehua; Li, Jiamin; Shang, Yan; Hu, Guoheng (Frontiers in Medicine, 2021)
Background: No specific treatment is available for postoperative cognitive dysfunction (POCD). Recently, interest in the prevention of POCD during the perioperative period has increased. While some studies suggest that transcutaneous electrical acupoint stimulation (TEAS) may be beneficial, the relevant evidence remains uncertain. Objective: To evaluate the preventive effects of TEAS on POCD. Methods: Seven databases including PubMed, EMBASE, CENTRAL, China National Knowledge Infrastructure (CNKI), Chinese Scientific Journal Database (VIP), Wanfang Database, and Chinese Biomedical Literature Database (CBM) were electronically searched up to April 2021. Two reviewers independently selected the studies, collected data, and assessed the risks of bias and GRADE certainty of the evidence. A meta-analysis of the incidence of POCD, cognitive function score, pain, adverse reactions, and length of hospital stay after surgery was also performed. Results: Twenty-nine randomized controlled trials with 1994 participants were included. The results of the meta-analysis showed that the TEAS group has a significantly lower incidence of POCD compared to the control group on postoperative days 1 [OR = 0.33 (95%CI: 0.23, 0.47); P < 0.001, I2 = 0%, moderate certainty], 3 [OR = 0.38 (95%CI: 0.29, 0.50); P < 0.001, I2 = 0%, low certainty], and 7 [OR = 0.51 (95%CI: 0.32, 0.81); P = 0.005, I2 = 0%, low certainty] but not on day 5 (P > 0.05, low certainty). Moreover, TEAS improved the Mini-Mental State Examination scores on postoperative days 1, 3, and 7 [MD = 2.44 (95%CI: 1.61, 3.27); P < 0.001, I2 = 93%, low certainty]; [MD = 2.07 (95%CI: 1.53, 2.62); P < 0.001, I2 = 87%, low certainty]; and [MD = 0.49 (95%CI: 0.18, 0.79); P = 0.002, I2 = 21%, low certainty], respectively, but not on day 5 (P > 0.05, very low certainty). TEAS promoted a postoperative analgesic effect within 24 h after surgery. Furthermore, patients receiving TEAS showed a lower incidence of postoperative nausea and vomiting and a shorter hospital stay. Conclusions: Limited evidence suggests that the application of TEAS in the perioperative period is associated with a reduced POCD rate and protected early postoperative cognitive function.